2017
DOI: 10.1016/j.jfs.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of macroprudential policies

Abstract: BIS Working Papers are written by members of the Monetary and Economic Department of the Bank for International Settlements, and from time to time by other economists, and are published by the Bank. The papers are on subjects of topical interest and are technical in character. The views expressed in them are those of their authors and not necessarily the views of the BIS.This publication is available on the BIS website (www.bis.org).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(154 citation statements)
references
References 45 publications
8
143
0
3
Order By: Relevance
“…Nevertheless, it is possible that even in the short term tighter restrictions on bank foreign borrowing (as discussed here) may lead to a shift in the behavior of the nonfinancial private sector which is such that it weakens the performance of these controls. A related issue is the possibility that, as documented by Bruno, Shim and Shin (2015), controls on some types of inflows may lead over time to substitution or spillover effects. A key question then is whether there are important gains from capital controls despite the existence of leakages or cross-flow effects, and more generally given the ability of the financial system to circumvent regulatory and prudential standards.…”
Section: Cyclically Adjusted Provisioning Rulesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is possible that even in the short term tighter restrictions on bank foreign borrowing (as discussed here) may lead to a shift in the behavior of the nonfinancial private sector which is such that it weakens the performance of these controls. A related issue is the possibility that, as documented by Bruno, Shim and Shin (2015), controls on some types of inflows may lead over time to substitution or spillover effects. A key question then is whether there are important gains from capital controls despite the existence of leakages or cross-flow effects, and more generally given the ability of the financial system to circumvent regulatory and prudential standards.…”
Section: Cyclically Adjusted Provisioning Rulesmentioning
confidence: 99%
“…Because smoothing financial cycles is a common problem, addressing this challenge will benefit a wide range of countries. At the same time, it is important to keep in mind that, as documented by Bruno, Shim and Shin (2015), macroprudential policies tend to be more successful when they complement monetary policy (by reinforcing monetary tightening) than when they act in opposite direction. Thus, the issue of coordinating monetary and macroprudential policies, possibly in the context of an integrated inflation targeting regime (as discussed by Agénor and Pereira da Silva, 2013), must also be addressed.…”
Section: Policy Lessonsmentioning
confidence: 99%
See 1 more Smart Citation
“…To be sure, they can be more targeted. And they can help relieve pressure on currency appreciation, which may in turn fuel risk-taking where foreign currency borrowing is widespread (Borio et al (2011), Bruno andShin (2014), Bruno et al (2015)). Even so, there is a certain tension in pressing on the accelerator and brake at the same time, such as when loosening monetary policy while seeking to offset its impact on financial instability through macroprudential measures.…”
Section: /17mentioning
confidence: 99%
“…Macroprudential policies can be divided into borrower-based (caps on LTV and DTI ratio) and lender-based, but it has been shown that for East Asia, borrower-based income has been used extensively and showed some impact (Cerutti, Claessens, and Laeven 2015;Bruno, Shim, and Shin 2015).…”
Section: Macroprudential Indexmentioning
confidence: 99%